2024
DOI: 10.1186/s12983-024-00527-1
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering the unusual, solitary bryozoan Monobryozoon ambulans Remane, 1936: first molecular and new morphological data clarify its phylogenetic position

Thomas Schwaha,
Sebastian H. Decker,
Christian Baranyi
et al.

Abstract: Background One of the most peculiar groups of the mostly colonial phylum Bryozoa is the taxon Monobryozoon, whose name already implies non-colonial members of the phylum. Its peculiarity and highly unusual lifestyle as a meiobenthic clade living on sand grains has fascinated many biologists. In particular its systematic relationship to other bryozoans remains a mystery. Despite numerous searches for M. ambulans in its type locality Helgoland, a locality with a long-lasting marine station and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Monobryozoidae was traditionally placed either among arachnidioids, primarily due to the presence of non‐kenozooidal cystid appendages (Jebram, 1986 ), or as incertae sedis (D'Hondt, 1983 ). More recent investigations suggest an affinity of monobryozoids with alcyonidioids (Schwaha, 2020c ; Schwaha et al., 2024 ), which is also confirmed in our study. This affinity is reflected by alcyonidioid‐like characters such as a circular orifice, the presence of a prominent orifical sphincter and a vestibular anus (Schwaha, 2020c ; Schwaha et al., 2024 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Monobryozoidae was traditionally placed either among arachnidioids, primarily due to the presence of non‐kenozooidal cystid appendages (Jebram, 1986 ), or as incertae sedis (D'Hondt, 1983 ). More recent investigations suggest an affinity of monobryozoids with alcyonidioids (Schwaha, 2020c ; Schwaha et al., 2024 ), which is also confirmed in our study. This affinity is reflected by alcyonidioid‐like characters such as a circular orifice, the presence of a prominent orifical sphincter and a vestibular anus (Schwaha, 2020c ; Schwaha et al., 2024 ).…”
Section: Discussionsupporting
confidence: 92%
“…More recent investigations suggest an affinity of monobryozoids with alcyonidioids (Schwaha, 2020c;Schwaha et al, 2024), which is also confirmed in our study. This affinity is reflected by alcyonidioidlike characters such as a circular orifice, the presence of a prominent orifical sphincter and a vestibular anus (Schwaha, 2020c;Schwaha et al, 2024).…”
Section: Benedeniporoidea As Early Protoctenostome and All Remainingsupporting
confidence: 92%
See 2 more Smart Citations